EFL Learners’ Motivation in Writing Their Undergraduate Thesis - Tasdiq Jibran Prameswara; Astri Hapsari (Indonesian TESOL Journal, 2023)
This study aims to describe the motivation of EFL undergraduate students to write their undergraduate thesis. The data were gathered through Zoom-mediated interviews with two participants: Ani, who had completed her undergraduate thesis and Budi, who was completing undergraduate thesis writing when the study was conducted. The data were analysed using thematic analysis. The findings reveal that both participants experienced amotivation, extrinsic motivation and intrinsic motivation while working on their undergraduate thesis. As they were proceeding towards finishing their undergraduate thesis, audiences comprising their parents, friends and lecturers provided them with encouragement, which in turn increased their motivation. The urges towards and interest in the topic also enhanced their motivation in writing their thesis. Thus, this study implies that the students need both external support and internal self-determined motivation in order to finish their undergraduate thesis writing. It suggests that topic familiarity is crucial in building students’ intrinsic motivation. Thus, students should be directed to link the topic, keywords, and construction or variables before they come into research methodology and present their findings.Keywords: EFL writing, motivation, undergraduate thesis